1995
DOI: 10.1002/jnr.490420214
|View full text |Cite
|
Sign up to set email alerts
|

Calpain secreted by activated human lymphoid cells degrades myelin

Abstract: Calpain secreted by lymphoid (MOLT-3, M.R.) or monocytic (U-937, THP-1) cell lines activated with PMA and A23187 degraded myelin antigens. The degradative effect of enzymes released in the extracellular medium was tested on purified myelin basic protein and rat central nervous system myelin in vitro. The extent of protein degradation was determined by SDS-PAGE and densitometric analysis. Various proteinase inhibitors were used to determine to what extent protein degradation was mediated by calpain and/or other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…In fact, the calpain and IFN-␥ labeling appeared to obscure the cell borders. These observations suggest that activated T cells may secrete calpain in vivo, confirming previous studies demonstrating cellular release of calpain in the presence of stimulatory factors (10,36,37). Activated T cells therefore may secrete calpain in EAE.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In fact, the calpain and IFN-␥ labeling appeared to obscure the cell borders. These observations suggest that activated T cells may secrete calpain in vivo, confirming previous studies demonstrating cellular release of calpain in the presence of stimulatory factors (10,36,37). Activated T cells therefore may secrete calpain in EAE.…”
Section: Discussionsupporting
confidence: 89%
“…In vitro studies have demonstrated vesicular disruption of the myelin sheath, as seen in demyelinating diseases, when rat sciatic nerves are exposed to calcium ionophores at physiological pH (31). Activated calpain also participates in programmed cell death in certain cell types, but reports of (10). Using fluorescent double-labeling techniques with both anti-CD2 and IFN-␥ antibodies, we found little calpain expression in CD2-positive cells, but markedly increased calpain immunoreactivity in cells expressing IFN-␥, which is produced by activated T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myelin proteins also may be degraded by calpain secreted from activated glial͞inflammatory cells because calpain is activated at extracellular calcium levels. Previous in vitro and in vivo studies have observed calpain secretion from various cell types, including activated macrophages and T cells, with subsequent degradation of myelin proteins (26,(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Activated calpain may be released from these cells (e.g. microglia, macrophages, T cells), thereby producing immunogenic peptides from digested myelin proteins for presentation to and sensitization of other T lymphocytes (Deshpande et al, 1995b;Smith et al, 1998).…”
Section: Introductionmentioning
confidence: 99%